REALIZATION OF THE COEVOLUTION IN THE PROCESS OF COMPLEX SYSTEM SELF-ORGANIZATION - Sh. M. Aliev (Юг России: экология, развитие)
Methodological basis of the process of integration of scientific knowledge is the interdisciplinary direction of the research which important component is the synergetrics. It plays an important role in the concept of coevolution realization which considers mutual relation of the person and the nature.